Analisis Media Social Marketing terhadap Loyalitas Pelanggan dalam Menggunakan Produk Kecantikan Benings - Handori; Handayani, Agustia; Wimbawani, Wiwik (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2024)
This study aims to analyze the influence of social media marketing on customer loyalty in using Bening's beauty products. The increasing use of social media in marketing strategies has become a significant concern, especially in the highly competitive beauty industry. The social media marketing variables examined include electronic word of mouth (e-WOM), social media marketing activities, and popular content. This research employed a quantitative associative method with a survey approach by distributing questionnaires to 310 respondents who are users of Benings products across Indonesia. The sampling technique used was simple random sampling. The results show that all three independent variables—e-WOM, social media marketing activities, and popular content—have a positive and significant influence on customer loyalty. These findings indicate that social media plays a crucial role in building and maintaining customer loyalty toward Bening's beauty products